ADAPTIVE LOCAL OPTIMUM DETECTOR - HU JACAO; CHEN YUANHENG (1986)
This invention uses the character istics of noise-wave probability density function in radar system, that is, the end of the function is higher than the end of Gaussian function and lower than the end of Laplace density function and real environmental noise-wave probabrlity distribution F(x) for forming a Reyleigh density function fr(x). This detector has simple structure and especially adapts to the situation of weak signal, anybody can operate easily without learning and training. It also has other properties and advantages of adaptation and dynamic range compression. The invention resolves the subject of optimum detecting weak definite known signal in high level, variation with time in large intensity time change and non-Gaussian noise-wave.